Fire in residence in the City of Recife: An experimental study - Corrêa, Cristiano; Braga, George Cajaty; Junior, Jose Bezerra; do Rêgo Silva, José Jeferson; Tabaczenski, Roberta; Pires, Tiago Ancelmo (Revista ALCONPAT, 2017)
This article presents the results of an experimental research, of a fire in dormitory of buildings typically burned in Recife city – Brazil. A room in the workshop of the Firemen Corporation, in a structure of reinforced concrete with a fence of ceramic bricks, has been used; such room has been remade and adapted for the research. This compartment has been prepared with furniture and objects generally found in fires happened in the city during the period between 2011 and 2013. They have made 24 thermic admeasurements with type K thermocouples, looking for the thermic behavior in the dormitory, in the furniture and walls, in both internal and external sides. The experiment has been monitored through VHS images and thermic camera, showing an effective cooling down on the walls with atomized flush, applied by the firefighting team.